Linking entrepreneurial orientation to firm performance: the role of differentiation strategy and innovation performance - Zehir, Cemal; Can, Esin; Karaboga, Tugba (ELSEVIER SCIENCE BV, 2015)
In the strategy literature, the effect of entrepreneurial orientation (EO) on firm performance has been investigated in many studies. The latest researches investigate the relationship between them by considering the effects of third variables which can be internal and external factors. Within this framework, our study focuses on the mediating role of innovation performance and differentiation strategy on the relationship between entrepreneurial orientation and firm performance. The survey of this study is conducted on 991 middle and senior managers of 331 middle and large scale firms operating in manufacturing industry in Turkey, in 2014. The data gathered from questionnaires are analyzed with SPSS statistical package program at firm level. The results of analyses showed that both differentiation strategy and innovation performance mediate the relationship between EO and firm performance. Also, analyses results revealed another mediating effect in which differentiation strategy mediates the relationship between EO and innovation performance.
Keywords: Entrepreneurial orientation; Differentiation strategy; Innovation performance; Firm performance; CORPORATE ENTREPRENEURSHIP; BUSINESS PERFORMANCE; MARKET ORIENTATION; LEARNING ORIENTATION; CONSTRUCT; DIMENSIONS; RESOURCES; Business & Economics; Social Sciences - Other Topics